Pola Tanam Dan Struktur Pendapatan Rumahtangga Petani Lahan Kering Di Zona Penyangga Kawasan Ekomomi Khusus Mandalika - Candra Ayu; Ibrahim Ibrahim; Nurtaji Wathoni; Pande Komang Suparyana (Universitas Mataram, 2026)
The Mandalika Special Economic Zone (KEK) was developed to accelerate equitable development in the region and its surrounding areas as a buffer zone. This study aims to identify cropping patterns and crop types, analyze the income structure of farming households in the buffer zone of the Mandalika KEK, Central Lombok Regency. The study used a descriptive method with the unit of analysis being farmer households. The research locations were determined purposively in Sengkol, Rembitan, and Sukadana Villages based on their dryland farming potential. A total of 45 respondents were selected using quota sampling. Data were analyzed using cost and income analysis and descriptive analysis. The results showed that farming households diversified their economic activities, with a combination of farmers and livestock breeders as the dominant productive activity (35.56%). The cropping pattern consisted of food crops in the first planting season and secondary crops, especially corn and soybeans, in the second planting season. The average household income was Rp29,059,273.03 per year, with agricultural activities contributing 60.33%, non-agricultural activities 36.80%, and other sources 2.87%. The main constraints on farming include scarcity of production inputs, particularly fertilizer, low intensity of extension services, limited capital, and pest and disease attacks. Findings indicate that agriculture remains the primary source of income for farming households, so strengthening access to production inputs, extension services, and capital is necessary to support the sustainability of dryland farming in the Mandalika Special Economic Zone buffer zone.